Pemanfaatan sukun muda untuk peningkatan nilai gizi abon ikan tongkol - Eva Fitriyaningsih (Politeknik Kesehatan Kemenkes Aceh, 2021)
Background: Using young breadfruit to increase the breadfruit usability and economic value, one of the efforts is through the enrichment of the type of processed breadfruit products, breadfruit provides nutritional value that is beneficial to health, one of the help of breadfruit is increasing breadfruit for shredded products.Objectives: This study aims to find out how to improve young breadfruit 20%, 30%, 40% of the chemical properties (carbohydrate, protein, and fiber) of shredded tuna.Methods: This study used an experimental design with a non-factorial Completely Randomized Design (CRD) with three preparations and three repetitions. Then the chemical tests (carbohydrate, protein, and fiber) at the Laboratory of Animal Nutrition and Feed Technology of the Faculty of Agriculture, Syiah Kuala University, Banda Aceh.Results: The study results showed actual participation in young breadfruit 20%, 30%, and 40% of the chemical properties (carbohydrate, protein, and fiber) in shredded tuna with a p-value < 0.05.Conclusion: Agreeing that 20%, 30%, and 40% of young breadfruit were approved for shredded tuna's chemical properties (carbohydrate, protein, and fiber).